From 3D to 4D printing with flexible resin - Chen, Shuo (Nanyang Technological University, 2022)
The ability to shape memory polymers (SMPs) and the development of 3D printing technology have fueled the progress of 4D printing. The properties of the SMPs, together with the suitable response stimuli, help the application of 4D printing proliferates in various industries such as dental and surgical healthcare. This project focus on the thermoset SMP from 3D printing to 4D printing to study the elastic property and the influence of the temperature. The flexible parts were printed by Stereolithography (SLA), which is one of the Vat Photopolymerization 3D printing processes, to study the recovering steps from the “freezing stable” state of the deformed shape to the original shape. The controllable recovery sequence was studied and analyzed to achieve the prediction of progressive recovery.